Documentation of ethnomedicinal knowledge of native flora utilized by Bishnupriya Manipuri people of Tripura, India - Dhar, Chayan; Bhagawati, Mayuri; Debnath, Barnita; Datta, Badal Kumar (Ethnobotany Research and Applications, 2025)
Background: Traditional medicinal knowledge remains integral to healthcare among indigenous communities, yet it is increasingly threatened by modernization and the decline of oral traditions. The Bishnupriya Manipuri community in Tripura, India, has a longstanding tradition of using native plants to treat diverse ailments. This study documents and analyses their ethnomedicinal practices and evaluates the therapeutic potential of locally used species across four districts—Sipahijala, Dhalai, Unakoti, and North Tripura. Methods: From April 2024 to January 2025, ethnobotanical surveys were conducted in 13 villages and one municipal area. Structured interviews with 150 participants, including elderly residents and traditional healers (Maipas), recorded plant species, families, local names, plant parts used, preparation methods, and administration routes. Data were analysed using descriptive statistics and quantitative indices—Use Value (UV), Family Use Value (FUV), Relative Frequency of Citation (RFC), Informant Consensus Factor (ICF), and Fidelity Level (FL). Results: A total of 82 medicinal species from 42 families were identified, with Lamiaceae, Asteraceae, and Fabaceae being dominant. Herbs were the most common growth form (44%), leaves the most used plant part (43.75%), and oral administration the preferred route (61%). Polygonum odoratum had the highest RFC (0.826) and FL (79.33%). Respiratory and endocrine disorders exhibited the highest ICF values, indicating strong consensus among informants. Conclusions: The findings highlight the Bishnupriya Manipuri community’s rich ethnomedicinal heritage and identify culturally important species with promising pharmacological potential. This work supports both the preservation of indigenous knowledge and the promotion of biodiversity-based, sustainable healthcare solutions. Keywords: Bishnupriya manipuri, ethnomedicine, medicinal plants, traditional knowledge, Tripura